The Role of the Religious Harmony Forum (FKUB) in Providing Recommendations for the Establishment of Houses of Worship in the City of Surabaya - Windy Aprilia Dewi; Agus Widiyarta (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The Religious Harmony Forum (FKUB) has a strategic role in maintaining social harmony, especially in terms of providing recommendations for the establishment of places of worship. This research aims to describe the role of the Surabaya City FKUB in providing recommendations for the establishment of places of worship, as well as the challenges and strategies faced in this process. This research uses a qualitative descriptive method, this research collects data through interviews, observation and literature study. The research results show that the Surabaya City FKUB has a major role in verifying and providing recommendations regarding the feasibility of establishing a place of worship. However, the challenges faced include protests from the community and ineffective coordination between related parties. To overcome this, FKUB implemented strategies such as inter-religious dialogue, increasing capacity, and improving coordination. This effort aims to create a harmonious and tolerant social life, as well as ensuring the licensing process runs smoothly. Keywords: Harmony between religious communitie, Places of worship, Religious Harmony Forum (FKUB)